State investment in science and scientific productivity of universities - Domagoj Karacic; Ivan Miskulin; Hrvoje Serdarusic (UTMS Journal of Economics, 2016)
State investment in service activities of the public sector, as well as the financial returns analyzed from the aspect of service effectiveness and utilization of public goods, can be considered as one of the most significant dilemmas, especially in the field of education. When analyzing state investments, through investment in education and development of the university, we can conclude that state investments in scientific productivity of universities fall into one of the main future frameworks of measurability of universities efficiency. This criterion cannot be taken as the most important since universities are fundamentally divided into teaching and research activities. However, the concept of determination of the productivity of universities, from the aspect of the scientific activities of the teaching staff, has an increasingly important role due to the specified global criteria and conditions for career advancement of the teaching staff and positioning of the university in the education market. This paper intends to give the overview of the current situation of universities in Croatia, as well as the trends that would point out state role in financing of universities and indicate coherent criteria regarding the financing of scientific productivity of teaching stuff.
Keywords: I22; E23; I28; 330; funding; government; research productivity; university research